Degree of Soft Tissue Injury is a Major Determinant of Successful Arterial Repair in the Extremity: A New Classification of Extremity Arterial Injury? - Peijun Deng; Jiantao Yang; Jacques Henri Hacquebord; Bengang Qin; Honggang Wang; Ping Li; Liqiang Gu; Jian Qi; Qingtang Zhu (Journal of Investigative Surgery, 2022)
Background This study aimed to investigate outcomes after extremity arterial injury repair and examined the association between outcomes and the degree of soft tissue injury and vascular repair methods. Methods A retrospective study was conducted on 106 patients (108 cases) who underwent emergent microsurgical repair of extremity arterial injury due to trauma and non-perfusion of the affected extremity. The cases were divided into three groups by degree of associated soft tissue injuries: (A) adequate soft tissue coverage over the injured major vessels after radical debridement, (B) inadequate soft tissue coverage over the injured major vessels after radical debridement, and (C) radical debridement was not feasible due to unclear extent of injured soft tissue. Differences in vascular repair methods and outcomes among the three groups were analyzed. Results In Group A (n = 61), microvascular suture and vessel graft achieved 95.1% and 85.0% successful limb reperfusion, respectively. In Group B (n = 31), vessel reconstruction with flap coverage achieved 100% successful reperfusion. Vessel graft achieved 28.6% successful limb reperfusion, while there were no cases of successful reperfusion using microvascular sutures. In Group C (n = 16), no vascular repair method achieved successful reperfusion. There were significant differences among the three groups in successful reperfusion (p < 0.001) and limb salvage (p < 0.001). Conclusion The extent of associated soft tissue injury was associated with different vascular repair methods and outcomes. We propose a new system for classifying these injuries according to the degree of associated soft tissue injury.